Latent damage generation in thin oxides of metal-oxide-semiconductor devices under high-field impulse stress and damage characterization using low-frequency noise measurement - Chim, W.K. (2014)
Japanese Journal of Applied Physics, Part 1: Regular Papers and Short Notes and Review Papers